Electric Field Induced Biomimetic Transmembrane Electron Transport Using Carbon Nanotube Porins (Small 32/2021). Issue 32 (12th August 2021) - Hicks, Jacqueline M.; Yao, Yun‐Chiao; Barber, Sydney; Neate, Nigel; Watts, Julie A.; Noy, Aleksandr; Rawson, Frankie J.
Abstract : Carbon Nanotube Porins In article number 2102517, Frankie J. Rawson and co‐workers report the use of carbon nanotube porins (CNTPs) as voltage dependant‐anion channel mimics. CNTPs are inserted into the membrane of neuronal cells. On applying an electric field, gold ions are reduced at the membrane interface containing the CNTPs via low voltage bipolar electrochemistry. Image credit: Dr. Leonora Martínez Núñez.